Smoke Distribution Patterns Analysis on Meteorological Conditions on Kalimantan Island Related to Forest and Land Fires: A Case Study Forest Fires In September 2019 - Pandapotan, Ivan Bachtiar; Komang Ngurah, Suarbawa; Widagda, I Gusti Agung (BULETIN FISIKA, 2021)
A r esearch has been carried out regarding forest and land fires that occurred in the Kalimantan area in September 2019. Meteorological factors such as rainfall, humidity, air temperature, speed and wind direction are parameters that can affect the process of fire occurrence and smoke distribution. In this study, meteorological data and smoke images from BMKG Tuban, Bali were used which were processed and analyzed so that they could be used to interpret meteorological conditions and smoke patterns on the island of Kalimantan. The smoke image that has been collected is processed using HYDRA software on channels 1, 2, and 7 and SATAID software on channels 3, 4, and 6 so that the color of the smoke and the distribution of smoke from forest fires will be visible in the form of images. Based on the results of the study, it can be concluded that the meteorological factors that cause forest fires are rainfall which quite low/minimal, temperature with an average of >30?, air humidity of 70%-80%, and the pattern of smoke spread is caused by winds moving from east to westward at a speed of 10 km/h to 37.04 km/h.